Review of The Multiplier Algebra of Orlicz Spaces - Mahmoud Masri (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this review of the paper of A. Hakawati, "The Multiplier Algebra of Orlicz Spaces" we point out a gap in the proof of the main result and suggest a proof of it. , We also point out some misprints.